Woodberry Down Health Centre, 1952 (London, 1952)
1952 1951-1960 "Woodberry Down Health Centre, 1952" [BW0133], 1952, Trades Union Congress Health centres were seen as a key feature in the reconstruction of health services introduced in the 1946 National Health Service Act. The London County Council built the first NHS centre on the Woodberry Down housing estate in Hackney. The building housed a whole range of medical services as well as a day nursery.